Identifying factors influencing rice production and consumption in Indonesia - Abdul Bashir; Saadah Yuliana (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
This study analyzes factors affecting rice production and consumption in Indonesia from 1990-2014, the data source is from Central Bureau of Statistics (BPS). The method used is model of multiple linear regression equation with ordinary least square estimator (OLS). Our findings indicate that rice production can be affected by human capital, labor, wages, wetland, urban population, and rice prices; on the other side, technology has no effect on rice production. Other findings on the rice consumption model were influenced by human capital, per capita income, population, and consumption the previous year, and meanwhile, rice prices has no effect to rice consumption in Indonesia. It’s an important note for the government in making the right program policies such as the development of better irrigation systems, empowering the farmers by providing regular training, subsidizing material inputs to farmers, expanding farmland for farmers. Meanwhile, the government needs to create policy such as food diversification, price stabilization security, the increase of rice stock, and other agricultural policies.